2008
DOI: 10.1016/j.ijdevneu.2008.11.007
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular guanosine and GTP promote expression of differentiation markers and induce S‐phase cell‐cycle arrest in human SH‐SY5Y neuroblastoma cells

Abstract: SH-SY5Y neuroblastoma cells, a model for studying neuronal differentiation, are able to differentiate into either cholinergic or dopaminergic/adrenergic phenotypes depending on media conditions. Using this system, we asked whether guanosine (Guo) or guanosine-5'-triphosphate (GTP) are able to drive differentiation towards one particular phenotype. Differentiation was determined by evaluating the frequency of cells bearing neurites and assessing neurite length after exposure to different concentrations of Guo o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
47
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(53 citation statements)
references
References 42 publications
3
47
0
1
Order By: Relevance
“…The human SH-SY5Y neuroblastoma cell line expresses a functional P2X7 receptor that modulates voltage-dependent Ca 2+ channel function [549]. Extracellular guanosine and guanosine triphosphates promote the expression of differentiation markers and induce S-phase cell cycle arrest in SH-SY5Y cells [550]. Agonistinduced stimulation of both A 1 and A 2A receptor induced neurite outgrowth and differentiation of SH-SY5Y neuroblastoma cells in vitro [551].…”
Section: Neuroblastoma/neuromamentioning
confidence: 99%
“…The human SH-SY5Y neuroblastoma cell line expresses a functional P2X7 receptor that modulates voltage-dependent Ca 2+ channel function [549]. Extracellular guanosine and guanosine triphosphates promote the expression of differentiation markers and induce S-phase cell cycle arrest in SH-SY5Y cells [550]. Agonistinduced stimulation of both A 1 and A 2A receptor induced neurite outgrowth and differentiation of SH-SY5Y neuroblastoma cells in vitro [551].…”
Section: Neuroblastoma/neuromamentioning
confidence: 99%
“…In line with the proposed neuritogenic properties of guanosine, a study conducted by Guarnieri et al sought to investigate whether this nucleoside was capable of promoting a mature neuronal phenotype in human SH-SY5Y neuroblastoma cells [55]. Gene profiling revealed that guanosine is able to induce an S-phase cell cycle arrest and neurite outgrowth that are comparable to those elicited by well-known inducers of neuronal differentiation, such as retinoic acid and phorbol-12-myristate-13-acetate (PMA).…”
Section: Neuritogenic Effects Of Guanosinementioning
confidence: 99%
“…This may be associated with the expression of cyclin E and suppression of cyclin B level. A recent report reveals that upregulation of cyclin E and concurrent downregulation of cyclin B prevent S phase exit [20]. This may be the main event that MSP-treated Colo 320DM cells are arrested at S phase rather than G2/M phase.…”
Section: Discussionmentioning
confidence: 96%
“…MSP arrests cell cycle of SW480 cells in G1 phase, which associates with downregulation of cyclin D1 and E and upregulation of p21. Not the same as SW480 cells, Colo 320DM cells are arrested by MSP treatment in S phase of cell cycle, which may be from the upregulation of cyclin E and downregulation of cyclin B [20]. Cyclin D1 and cyclin E are both key regulators to CDK4 and 6, which phosphorylate retinoblastoma protein and results in retinoblastoma protein to degeneration.…”
Section: Discussionmentioning
confidence: 99%